FORMULATION OF CHEWABLE TABLET PREPARATIONS FROM THE COMBINATION OF Azadirachta Indica A. Juss. AND Gynura Procumbens (Merr.) - Nofran Putra Pratama; Kurnia Rahayu Purnomo Sari; Endah Kurniawati (Universitas Muhammadiyah Magelang, 2022)
Azadirachta indica A. Juss. and Gynura procumbens (Merr.) are one type of potential medicinal plants because they have various properties. One of the properties of these two plants is as an antioxidant. The combination of the two plants has a strong category of antioxidant activity, does not cause death and physical changes in test animals. This study aimed to make an antioxidant chewable Tablet containing a combination of Azadirachta indica A. Juss. and Gynura procumbens (Merr.) extract with a variation of mannitol-sorbitol as a filler. This variation has the advantage of covering the bitter taste of the active substance so that it is expected to provide a pleasant taste and is easy to swallow. The extract obtained was formulated into chewable Tablets with variations of mannitol-sorbitol (90%:10%), (80%:20%), and (70%:30%). The method used is wet granulation. The granules obtained were tested for their physical properties, namely flow velocity, angle of repose, and compressibility. The physical properties of the Tablets tested included uniformity of weight, size, hardness, friability, disintegration time, quality of taste, shape, and odor. Based on the test results of the physical properties of the granules, the three formulas met the requirements. While the physical properties of Tablets that do not meet the criteria are uniformity of size and disintegration time. This research concludes that the extracts of Azadirachta indica A. Juss. and Gynura procumbens (Merr.) be formulated into chewable Tablets where formula two with variations of mannitol:sorbitol (80:20%) is the best formula by fulfilling 9 of 11 requirements